European land settlement and development in Latin America: the evolution of an idea from Interwar to the early Post-WWII years - Papadopoulos, Yannis G.S.; Parsanoglou, Dimitris (Diálogos Latinoamericanos, 2022)
This article examines the birth and evolution of the idea of land settlement as a way to combine and resolve two issues diachronically considered problematic: on the one hand, the underdevelopment in Latin America due to a certain extent to the lack of labour force that could exploit the immense lands available; on the other hand, the overpopulation in Europe accompanied by volatile problems such as unemployment, particularly in critical times such as between and after the two World Wars. Based on archival material retrieved from the National Archives and Records Administration in Washington D.C., the Archives of the FDR Presidential Library and Museum in New York, the Archives of the IOM Office in Athens and the São Paulo State Archive, we attempt to provide a genealogy of this idea since the Interwar period and the ways in which it has materialised by governments and international organisations, namely the ILO and the ICEM.